Ziconotide and psychosis: from a case report to a scoping review - Peraire, Marc; Gimeno-Vergara, Rita; Pick-Martin, Jennifer; Boscá, Mireia; Echeverria, Iván (Frontiers in Molecular Neuroscience, 2024)
Ziconotide is a non-opioid analgesic that acts on N-type voltage-gated calcium channels. Despite its proven effectiveness in pain treatment, it can induce neuropsychiatric symptoms. The aim of this article is to present a case of psychosis secondary to ziconotide and to explore the variety of neuropsychiatric symptoms it produces, exploring the relationship between these symptoms and the mechanism of action of ziconotide. For this purpose, a clinical case is presented as well as a scoping review of other cases published in the scientific literature. A search on Web of Science, Pubmed and Embase databases was performed on December 11, 2023, following the criteria of the PRISMA-ScR Statement. The clinical case presented shows the variety of neuropsychiatric symptomatology that ziconotide can cause in the same patient. On the other hand, 13 papers were retrieved from the scoping review (9 case reports, 4 case series), which included 21 cases of patients treated with ziconotide who presented adverse effects ranging from psychotic symptoms to delirium. In conclusion, the variety of neuropsychiatric symptoms derived from ziconotide could be related to the blockade of N-type voltage-gated calcium channels in glutamatergic and GABAergic neurons, in turn affecting dopaminergic pathways.